Two Major Clades of Bradyrhizobia Dominate Symbiotic Interactions with Pigeonpea in Fields of Côte d'Ivoire - Fossou, Romain K.; Ziegler, Dominik; Zézé, Adolphe; Barja, François; Perret, Xavier (Frontiers in Microbiology, 2016)
In smallholder farms of Côte d’Ivoire, particularly in the northeast of the country, Cajanus cajan (pigeonpea) has become an important crop because of its multiple beneficial facets. Pigeonpea seeds provide food to make ends meet, are sold on local markets and aerial parts serve as forage for animals. Since it fixes atmospheric nitrogen in symbiosis with soil bacteria collectively known as rhizobia, C. cajan also improves soil fertility and reduces fallow time. Yet, seed yields remain low mostly because farmers cannot afford chemical fertilizers. To identify local rhizobial strains susceptible to be used as bio-inoculants to foster pigeonpea growth, root nodules were collected in six fields of three geographically distant regions of Côte d’Ivoire. Nodule bacteria were isolated and characterised using various molecular techniques including matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) mass spectrometry (MS) and DNA sequencing. These molecular analyses showed that 63 out of 85 nodule isolates belonged to two major clades of bradyrhizobia, one of which is known as the Bradyrhizobium elkanii super clade. Phylogenies of housekeeping (16S-ITS-23S, rpoB) and symbiotic (nifH) genes were not always congruent suggesting that lateral transfer of nitrogen fixation genes also contributed to define the genome of these bradyrhizobial isolates. Interestingly, no field-, plant- or cultivar-specific effect was found to shape the profiles of symbiotic strains. In addition, nodule isolates CI-1B, CI-36E and CI-41A that belong to distinct species, showed similar symbiotic efficiencies suggesting that any of these strains might serve as a proficient inoculant for C. cajan.